INDONESIAN LANDSCAPE PAINTING BASED ON ARTIFICIAL INTELLIGENCE (AI) VIEWPOINTS - Fahriza, Ba’im; Mujiyono (Universitas Negeri Semarang, 2025)
A landscape is a visual representation of an area that encompasses both natural and man-made elements. In the context of fine art, particularly painting, a landscape not only displays natural beauty but also implies aesthetic, cultural, and emotional values. The development of digital technology such as artificial intelligence has opened up new opportunities in the creation of paintings. This study project aims to produce an Indonesian landscape painting that presents visual freshness through an AI perspective. The methods used in the creation process include three main approaches: experiential AI, local aesthetics, and a naturalistic approach. The creation process is divided into three stages: pre-creation, creation, and post-creation. The resulting work is entitled